Maternal Methadone Destabilizes Neonatal Breathing and Desensitizes Neonates to Opioid-Induced Respiratory Frequency Depression - Hocker, Austin D.; Morrison, Nina R.; Selby, Matthew L.; Huxtable, Adrianne G. (Frontiers in Physiology, 2021)
PPregnant women and developing infants are understudied populations in the opioid crisis, despite the rise in opioid use during pregnancy. Maternal opioid use results in diverse negative outcomes for the fetus/newborn, including death; however, the effects of perinatal (maternal and neonatal) opioids on developing respiratory circuitry are not well understood. Given the profound depressive effects of opioids on central respiratory networks controlling breathing, we tested the hypothesis that perinatal opioid exposure impairs respiratory neural circuitry, creating breathing instability. Our data demonstrate maternal opioids increase apneas and destabilize neonatal breathing. Maternal opioids also blunted opioid-induced respiratory frequency depression acutely in neonates; a unique finding since adult respiratory circuity does not desensitize to opioids. This desensitization normalized rapidly between postnatal days 1 and 2 (P1 and P2), the same age quantal slowing emerged in respiratory rhythm. These data suggest significant reorganization of respiratory rhythm generating circuits at P1-2, the same time as the preBötzinger Complex (key site of respiratory rhythm generation) becomes the dominant respiratory rhythm generator. Thus, these studies provide critical insight relevant to the normal developmental trajectory of respiratory circuits and suggest changes to mutual coupling between respiratory oscillators, while also highlighting how maternal opioids alter these developing circuits. In conclusion, the results presented demonstrate neurorespiratory disruption by maternal opioids and blunted opioid-induced respiratory frequency depression with neonatal opioids, which will be important for understanding and treating the increasing population of neonates exposed to gestational opioids.